The ant genus Tetramorium Mayr (Hymenoptera: Formicidae) in the Malagasy region—introduction, definition of species groups, and revision of the T. bicarinatum, T. obesum, T. sericeiventre and T. tosii species groups - Garcia, Francisco Hita; Fisher, Brian L. (Zootaxa, 2011)
The globally distributed ant genus Tetramorium Mayr is especially diverse in the Afrotropical, Oriental, and Indo-Australian regions, while the Malagasy fauna, by contrast, seemed to be comparatively species-poor. However, recent ant inventories in Madagascar and its surrounding island systems have generated an immense amount of new material. As a result, there is now a great need of an updated taxonomic revision for the genus Tetramorium in this region. The present study represents an introduction to the genus, and treats the species groups encountered in the Malagasy region. All former species groups were redefined, and several new groups were established, in order to accommodate the substantial amount of new material. We propose 14 species groups of Tetramorium for this region. Morphological boundaries between these groups and their biogeographic affinities are discussed, and an illustrated identification key to species groups is provided. Diagnoses of all species groups are presented, as well as images of typical group members. Additionally, the species level taxonomy of the T. bicarinatum, T. obesum, T. sericeiventre and T. tosii species groups is revised with descriptions and images of all species, and an identification key to the species of the T. bicarinatum group is provided. No nomenclatorial changes are documented from the T. bicarinatum, T. obesum, and T. tosii groups. However, within the T. sericeiventre species group, one new species, T. mahafaly sp. n., is described and T. quadrispinosum Emery, 1886 and all its former synonyms are proposed as junior synonyms of T. sericeiventre Emery, 1877. At present, there are still 39 valid species of Tetramorium for the Malagasy region, but this number is expected to increase significantly with upcoming taxonomic revisions of the species groups not revised in this study.